Civil aircraft engine operation life resilient monitoring via usage trajectory mapping on the reliability contour. (February 2023) - Zhou, Hang; Farsi, Maryam; Harrison, Andrew; Parlikad, Ajith Kumar; Brintrup, Alexandra
Abstract: The civil aircraft engine business is complex in operation. Being an asset-heavy business operating highly complex engineering systems, the optimized fleet life-cycle management is essential yet challenging. The aviation systems are known for critical operation conditions, high-standard reliability demands, and high cost in both asset value and through-life maintenance services. Civil aircraft engines typically require 3 to 4 highly costly overhauls through service life to maintain performance and the time-on-wing (TOW) requirements of the airline operators. Multiple levels of maintenance activities need accurate and long-term planning for engine fleets coordinating manufacturing, transportation, supply chains and system performance, based on the service life of the engines. The life of assets in the aviation industry is measured uniquely by two scales — the flying hour (FH) and the flying cycle (FC). This paper proposed to evaluate the aviation systems' service life combining both FH and FC, and the reliability of the systems be dynamically quantified via the records and future plans of the flight profiles. The long-term planning of the most significant shop visit (SV) overhauls is therefore optimized by maximizing the fleet TOW availability, considering the business model of 'charge customers by the flying time' in the civil aircraft engine business. Highlights: Evaluated the reliability of civil aircraft engine. Proposed to combine the Flying Cycle (FC) and Flying Hour (FH) by copula. Created the concept of reliability contour map. Developed operation life resilient monitoring technique via usage trajectory. Optimized the overhaul scheduling by maximizing fleet Time-on-Wing (TOW).